2014
DOI: 10.1016/j.tsf.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the degree of high power impulse magnetron sputtering utilisation on the structure and properties of TiN films

Abstract: TiN films were deposited using High Power Impulse Magnetron Sputtering (HIPIMS) enabled four cathode industrial size coating system equipped with HIPIMS power supplies. The standard version of this system allows control over the ion bombardment during coating growth by varying the strength of the electromagnetic field of the unbalancing coils and bias voltage applied to the substrate. The coatings were produced in different coating growth conditions achieved in combined HIPIMS-direct current (DC) unbalanced ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…While depositing the coatings, UBM-DC was combined with HIPIMS to achieve a higher deposition rate [15]. All multilayer CrN/NbN coatings were produced by operating one Cr and one Nb target in HIPIMS mode and the other two targets (1 Cr and 1 Nb) in UBM mode.…”
Section: Coating Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…While depositing the coatings, UBM-DC was combined with HIPIMS to achieve a higher deposition rate [15]. All multilayer CrN/NbN coatings were produced by operating one Cr and one Nb target in HIPIMS mode and the other two targets (1 Cr and 1 Nb) in UBM mode.…”
Section: Coating Depositionmentioning
confidence: 99%
“…Due to the denser microstructure and smaller grain size, HIPIMS deposited coatings exhibited lower surface roughness, higher hardness, improved adhesion, excellent wear and corrosion resistance [12][13][14]. Although the deposition rate during the HIPIMS process is quite low, this drawback can be eradicated by combining HIPIMS with the Unbalanced Magnetron Sputtering (UBM) process [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HIPIMS, the metal ion to neutral ratio is much higher which prevents the void formation and hence can be used to deposit void free dense coatings [35][36][37]102]. The benefits of using HIPIMS and a higher bias voltage can be observed from the [46]. This study suggested that sufficiently high metal ionisation can eradicate these defects (i.e.…”
Section: Types Of Defectsmentioning
confidence: 83%
“…It has been widely published that the HIPIMS technique is an excellent tool to deposit coatings with very dense structure without inter-columnar voids but shows a relatively lower deposition rate. On the other hand, the conventional UBM technique has higher deposition rate but can produce porous coatings [15,35,[46][47][48]. A combination of both techniques, however can eradicate these problems and produce coatings with a high deposition rate and very dense structure [46,49].…”
Section: Sputtering Technique (Hipims/ubm)mentioning
confidence: 99%